2000
DOI: 10.1007/s004200050429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration magnitude and repetitive exposure on finger blood flow in healthy subjects

Abstract: In order to study the effect of the magnitude of vibrations and repetitive exposure on finger blood flow, we exposed ten healthy subjects to three experimental conditions: (1) vibration of 3.16 m/s2 at 60 Hz, (2) vibration of 31.6 m/s2 at 60 Hz, and (3) no vibration, as a control. Under the experimental conditions, the right hand was exposed to 5-min vibration three times, with intervening 5-min rests. Meanwhile, the blood flows of both middle fingers were continuously measured with a blood flow meter based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…These observations appear to be consistent with the findings of several other studies, where the vasomotor effects induced by vibration, hence arteriolar blood flow, have been seen to depend on the amplitude of the accelerations transmitted to the hand surface 7,[30][31][32] . Increasing vibration magnitude, measured by an increase in root mean square acceleration magnitude, has been seen to enhance FBF reduction 7,31) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These observations appear to be consistent with the findings of several other studies, where the vasomotor effects induced by vibration, hence arteriolar blood flow, have been seen to depend on the amplitude of the accelerations transmitted to the hand surface 7,[30][31][32] . Increasing vibration magnitude, measured by an increase in root mean square acceleration magnitude, has been seen to enhance FBF reduction 7,31) .…”
Section: Discussionsupporting
confidence: 92%
“…Different durations and modes of exposure result in different vasoconstriction effects arising in different ways and lasting for different lengths of time 1,29,31) . A greater reduction in FBF after the test with the low grip occurred in both index fingers and in the right middle finger in 6 subjects, who were probably more susceptible than the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental high-frequency, low-magnitude vibrations reduce the number of blood vessels per muscle fiber [19]. Besides direct mechanical injury to motor nerves and muscle fibers, reduced blood flow due to impaired sensory feedback and metabolic changes has been proposed [17]. In an experimental study, Curry et al [18] showed that vibration caused decreased tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic vibrations and stretch during snoring might cause neuromuscular damage over time. Although it is not established that the morphological abnormalities in palate tissue of SDB patients is related to mechanical trauma during snoring, longstanding mechanical vibration and muscle stretch are known to cause nerve and muscle fiber damage in human limbs [13,14,15,16] and to impair the microcirculation in the exposed muscles in animals [17,18,19]. …”
Section: Introductionmentioning
confidence: 99%